IMPLEMENTATION OF CANVA-BASED MIND MAPPING TO IMPROVE STUDENTS' CREATIVITY ON INDEPENDENCE MATERIAL IN THE 1945-1950 PERIOD: Classroom Action Research in Class IX MTs. Ma'arif Peundeuy Garut - Tetep; Dianah, Lili; Dadang (SAHUR Journal, 2025)
The low level of student creativity in history learning, particularly regarding the topic of Indonesian independence during the 1945–1950 period, served as the background for this research. This is indicated by the lack of originality, flexibility, and elaboration skills in thinking and expressing ideas. The aim of this study is to describe the implementation of Canva-based Mind Mapping as a learning model, analyze the improvement in students' creativity, and identify obstacles and solutions in applying this method. This research employed a Classroom Action Research (CAR) approach with two cycles conducted in Class IX of MTs. Ma’arif Peundeuy Garut. The instruments used included observation, interviews, documentation, and tests. The results showed that the application of Canva-based Mind Mapping significantly improved students' creativity, as evidenced by their enhanced ability to express ideas, create engaging visualizations, and convey information systematically. These findings indicate that the use of digital media such as Canva can be an innovative and effective alternative for fostering student creativity.